2020
DOI: 10.1177/2372732219893385
|View full text |Cite
|
Sign up to set email alerts
|

How Reading Motivation and Engagement Enable Reading Achievement: Policy Implications

Abstract: Successful reading comprehension demands complex cognitive skills, and, consequently, motivation to make meaning from text. Research on reading motivation and engagement can inform policy aimed at improving reading achievement. Multiple dimensions of reading motivation and engagement—and instructional practices for bolstering each one—draw on interventions for students of diverse language and ethnic backgrounds in elementary and middle grade classrooms. The article concludes with policy recommendations centeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 43 publications
(71 reference statements)
0
44
0
2
Order By: Relevance
“…Autonomy support. First, students can choose the texts they want to read, based upon their personal interest (Patall et al, 2013;Su & Reeve, 2011;Taboada & Klauda, 2020). This is proven to be a driving force for reading comprehension growth (Retelsdorf et al, 2011;Soemer & Schiefele, 2019).…”
Section: Reading Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomy support. First, students can choose the texts they want to read, based upon their personal interest (Patall et al, 2013;Su & Reeve, 2011;Taboada & Klauda, 2020). This is proven to be a driving force for reading comprehension growth (Retelsdorf et al, 2011;Soemer & Schiefele, 2019).…”
Section: Reading Motivationmentioning
confidence: 99%
“…• Give students the opportunity to select the texts they will read Second, the value of reading is explicitly emphasized (Su & Reeve, 2011;Taboada & Klauda, 2020), mainly to tap into students' identified regulation (Jang, 2008;Ryan & Deci, 2020). In ProjectExpert, this is operationalized by using texts students will encounter in their daily life (e.g., job contract, medicinal product package leaflet), by highlighting the advantages of being a proficient reader in a for the students accessible way (e.g., via cartoons), and via class discussions based on videoclips of peer reactions about the value of reading.…”
Section: Feasibility and Usabilitymentioning
confidence: 99%
“…Similarly, for recommendation 4, the IES Guide recommends offering students choice of reading materials to develop autonomy and motivation. More recently, Barber & Klauda (2020) go further and offer specific recommendations on how teachers can structure their students’ choice readings and consider how choice intersects with other literacy goals. It is clear that educators relying only on the IES Guide’s vision would be unaware of the exciting findings of the last decade.…”
Section: Expanding On the Guide’s Five Recommendationsmentioning
confidence: 99%
“…Reading for pleasure (RfP) is an undervalued but highly beneficial practice conferring a range of educative and socio-emotional advantages. RfP can be conceptualised as 'volitional reading in which we choose to engage' (Kucirkova & Cremin, 2020, p. 2), and enjoyment of reading is associated with the development of literacy skills (Barber & Klauda, 2020;Ho & Lau, 2018;Lupo et al, 2017;Organisation for Economic Co-operation & Development, 2011;Rogiers et al, 2020;Schiefele et al, 2016). For example, Sullivan and Brown (2013) found that RfP offers benefits in vocabulary and spelling as well as mathematics, noting that 'reading for pleasure at the ages of 10 and 16 had a substantial influence on cognitive progress' (p. 2) in these areas.…”
Section: Introductionmentioning
confidence: 99%